Enhancing learning concentration in hyperactive children through brain gym activities at Wahyu Islamic Kindergarten - Aisyah, Fitri; Muslam, Muslam (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Children with hyperactivity or Attention Deficit Hyperactivity Disorder (ADHD) are those who experience difficulty in maintaining attention, tend to be impulsive, and display a high level of motor activity. This condition often poses challenges in the learning process, particularly in terms of concentration and focus during classroom instruction. One approach that is currently being widely developed to help improve learning concentration in hyperactive children is brain gym activities. Aim: This study aims to explain how brain gym activities can enhance the learning concentration of hyperactive children and to provide an overview of the benefits of brain gym as a non-pharmacological intervention to support hyperactive children in the learning process at Wahyu Islamic Kindergarten. Method: This research adopts a descriptive qualitative approach. Data collection was carried out through interviews, documentation, and observation. The research subject was one hyperactive child at Wahyu Islamic Kindergarten. The data analysis technique used was triangulation. Results: The results of the study indicate that brain gym activities serve as an effective method to increase learning concentration in hyperactive children. The child became more focused, enthusiastic, and motivated in learning. A distinguishing aspect of this study compared to previous research is that it specifically focuses on a child with hyperactivity, whereas earlier studies generally involved children without special needs. Thus, this study broadens the scope of brain gym benefits and opens up new intervention opportunities for children with special needs, a group often overlooked in prior research. Conclusion: Brain gym activities consist of simple movements performed according to the child’s abilities to stimulate brain development and enhance learning concentration in hyperactive children.